2015
DOI: 10.1177/1934578x1501001108
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Polyphenol Content of Some Brazilian Medicinal Plants Exploiting the Formation of the Fe(II)/2,2′-bipyridine Complexes

Abstract: Aqueous plant extracts contain polyphenols that reduce Fe 3+ to Fe 2+ , which in the presence of excess 2,2'-bipyridine (bipy) yield the Fe(bipy) 3 2+ complex (max = 521 nm). This reaction was used to quantify the total polyphenol content (TPC) of nineteen Brazilian medicinal species using pyrogallic acid (PA) as a standard. A calibration curve of absorbance values at 521 nm values vs. PA was linear from 0.378 to 3.03 mg L-1 (r = 0.998; n = 8) with a limit of detection 0.16 mg L-1. The TPC quantification usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Since antioxidants terminate direct reactive oxygen species attacks and radical‐mediated oxidative reactions, appear to be of primary importance in the prevention of these diseases and health problems. Antioxidants have been detected in a number of plants and foods, including seed oils (Kalt et al ., ; Iauk et al ., ; Munro et al ., ; Santana et al ., ). Hemp seed oil shows excellent oxidative stability suggesting the possible presence of phenolic compounds that act as antioxidants in the cold‐pressed seed oil (Abuzaytoun and Shahidi, ).…”
Section: Introductionmentioning
confidence: 97%
“…Since antioxidants terminate direct reactive oxygen species attacks and radical‐mediated oxidative reactions, appear to be of primary importance in the prevention of these diseases and health problems. Antioxidants have been detected in a number of plants and foods, including seed oils (Kalt et al ., ; Iauk et al ., ; Munro et al ., ; Santana et al ., ). Hemp seed oil shows excellent oxidative stability suggesting the possible presence of phenolic compounds that act as antioxidants in the cold‐pressed seed oil (Abuzaytoun and Shahidi, ).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies are found in the literature dealing with the determination of total polyphenol content (TPC) and the antioxidant capacity of Brazilian medicinal plant species (BLAINSKI; LOPES; MELLO, 2013;BRIGHENTE et al, 2007;HABERMANN et al, 2016;MANOEL;SANTANA;. Most of them investigated a unique part of the plant species (leaves, stem, seeds, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Considering this, minimizing oxidative damage may be one of the most important approaches to the primary prevention of chronic diseases and ageing-associated health problems. Antioxidants have been detected in several plants and foods, including seed oils [ 14 , 15 ]. HSO shows excellent oxidative stability, suggesting the possible presence of secondary metabolites with strong antioxidant activity [ 6 , 16 ].…”
Section: Introductionmentioning
confidence: 99%